Aplikasi Aceh Halal Recipe Berbasis Android - Ardiansyah, Haimi (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2022)
This paper focuses on designing and usability analysis of Aceh Halal Recipe based on android operating system. The research aims to support Aceh Government in establishing Aceh as Halal Tourism Destination in Indonesia. The Halal Tourism is one of main factors in attracting people around the world to come and visit Aceh. Therefore, it is required some supportive components and infrastructures in maintain Aceh being model for world halal tourism destination. The mobile application takes an important role in fulfilling the need of mobile generation. The application is designed to assist the people to find out Halal Food in Aceh through mobile platform. The application provides a number of information regarding Aceh foods for tourists or visitors. The researcher analyzes the human-computer interaction of Aceh halal recipe application in terms of the usability and efficiency. The application is used by people in different ages, backgrounds, and purposes. The method of gathering requirement is done to gather user experience from the defined users using qualitative approach. The methods are structured interview and scenario. The data that is collected then is analyzed before building the low fidelity prototype. Usability testing was done in two cycles using walkthrough method and then some further enhancement is done to the mobile application